2018
DOI: 10.1371/journal.pone.0200198
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of spinal alignment with muscular volume and fat infiltration of lumbar trunk muscles

Abstract: Fat infiltration and atrophy of lumbar muscles are related to spinal degenerative conditions and may cause functional deficits. Spinal alignment exerts biomechanical influence on lumbar intervertebral discs and joints. Our objective was to evaluate if spinopelvic parameters correlate with the lumbar muscle volume and fat infiltration. This is an observational, prospective and cross-sectional study. Ninety-three asymptomatic adult aged 20–40 years were included. Lumbar lordosis (LL), thoracic kyphosis (TK), pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 40 publications
0
27
3
Order By: Relevance
“…Research in asymptomatic individuals has shown a correlation between spinopelvic parameters and paravertebral muscle volume, although none of those parameters have been found to correlate with fatty infiltration of muscle (47) . The volume of the psoas muscle showed a positive correlation with the magnitude of the thoracic kyphosis, lumbar lordosis, and sagittal vertical axis (47) .…”
Section: Discussionmentioning
confidence: 96%
“…Research in asymptomatic individuals has shown a correlation between spinopelvic parameters and paravertebral muscle volume, although none of those parameters have been found to correlate with fatty infiltration of muscle (47) . The volume of the psoas muscle showed a positive correlation with the magnitude of the thoracic kyphosis, lumbar lordosis, and sagittal vertical axis (47) .…”
Section: Discussionmentioning
confidence: 96%
“…The psoas major muscle was the primary flexor of the hip joint. Xia et al demonstrated that there was no relationship between PT and the psoas muscle 36 ; whereas Menezes-Reis et al demonstrated that SVA was inversely correlated with the psoas volume 37 . Other studies have demonstrated that the magnitude of the multifidus and psoas muscle was negatively associated with the presence of a marked deformity 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Pressure against the anterior thigh from prone positioning during the surgery could also lead to thigh symptoms [ 22 ]. Moreover, degenerative spinal conditions and spinopelvic parameters were reported to affect the lumbar muscle volume, including psoas major as it originates from the transverse processes of T12–L5, and possibly cause functional deficits in the skeletal muscles [ 23 ].…”
Section: Discussionmentioning
confidence: 99%